Management Perspectives towards the Data-Driven Organization in the Energy Sector - Irina Bogdana Pugna; Dana Maria Boldeanu; Mirela Gheorghe; Gabriel Cozgarea; Adrian Nicolae Cozgarea (Energies, 2022)
This paper explores the current attitudes of managers and executives working in the energy sector towards the Data-Driven Organizational Model implied by Big Data. The aim is to explore and understand the current mindset of senior decision makers, since their success depends as much on cognitive and behavioral processes as on their technical competences. We adopt a grounded-theory approach, developing models of understanding and belief abductively, driven by the data obtained from participants through a reflection guide. We find that managers differ significantly in their understanding and engagement with their challenges; they display interest but differ in their commitment and enthusiasm; they identify a lack of strategy and skills as current barriers; and they are currently unwilling to trust data, treating evidence according to their own prior commitments. This is a significant barrier to establishing the Data-Driven Organizational Model. These findings raise concerns, and the paper concludes that by considering initiatives for implementing more agile and forward-looking approaches, establishing a data-driven organizational culture, and managing such changes effectively.